"FEATURES OF GENDER AND AGE-RELATED CHANGES IN ARTERIAL HYPOTENSION IN THE AGRICULTURAL POPULATION" (Conferencea, 2023)
The purpose of this study is to study the characteristics of gender and age-related changes in the epidemiology of arterial hypotension (ArGt) in the agricultural population.